Examining Prisoners’ Family Resilience - Wassalim, Figur Ronggo; Nizar, Muchamad Coirun; Madrah, Muna Yastuti (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
This study focuses on prisoners’ family resilience in the village of Tambakrejo, Semarang. Ideally, family resilience is achieved when the rights and obligations of the household are fulfilled. It is though difficult for prisoner’s families to reach such an ideal condition due to the absence of husbands/fathers. The absence of these important figures results in family vulnerability. By using the qualitative approach, this research explores the condition of seven prisoners’ families in Tambakrejo village, Semarang city. The results of this study indicate that the families of prisoners in Tambakrejo village seem to be resilient.  The prisoner’s families in Tambakrejo are resilient because of some factors.  First, there are strong commitment from both husbands and wives.  Second, the presence of the child encourages the marriage couples to hold firmly on their marriage commitment, and third, each party tries to always think positively about their respective partners. However, there are also inhibiting factors affecting families’ resilience, including family financial issues, communication problems, and social sanctions. Based on those indicators, the families of prisoners in Tambakrejo can be categorized as having a low level of family resilience. However, the integrity of prisoners’ families in Tambakrejo Semarang can be maintained with commitment and persistence in keeping the purpose of their marriage.